Analyzing the transient response dynamics of long-term depression in the mouse auditory cortex in vitro through multielectrode-array-based spatiotemporal recordings - Furukawa, Ryo; Kume, Kouta; Tateno, Takashi (Frontiers in Neuroscience, 2024)
In the auditory cortex, synaptic plasticity, including long-term potentiation (LTP) and long-term depression (LTD), plays crucial roles in information processing and adaptation to the auditory environment. Previous rodent studies have shown life-long cortical map plasticity, even beyond the critical period of development. While thalamocortical synapses exhibit LTD during the critical period, however, little is known about LTD in cortico-cortical connections of the adult mouse auditory cortex. Here, we investigated the transient response dynamics of LTD in layers 2 to 5 of the mouse auditory cortex following tetanic stimulation (TS) to layer 4. To characterize LTD properties, we developed a recording protocol to monitor activity levels at multiple sites, including those more than 0.45 mm from the TS site. This allowed us to distinguish LTD-induced reductions in neural excitability from other types, including neural activity depletion. Our findings revealed that LTD induced in layer 4 persisted for over 40 minutes post-TS, indicating robust cortico-cortical LTD. Using electrophysiological data and a modified synaptic model, we identified key receptors involved in synaptic plasticity and their effects on response dynamics, proposing a method for studying LTD in the mature mouse auditory cortex. Particularly, by employing a simple dynamical model, we analyzed and discussed the involvement of key receptors during the transient period of LTD. This study expands our understanding of synaptic plasticity in the mature mouse auditory cortex beyond the critical period, potentially informing future treatments for hearing disorders.